Analisis Pengelompokkan Pelanggan Menggunakan Algoritma K-Means - diana, yusvi; Hadi, Febri; Hadi, Meswantri (CV. ITTC INDONESIA, 2025)
The development of technology today has a great influence in various fields. One of the fields that requires information technology data processing is the business field. Information technology data processing is very necessary to analyze data in the business world. Data analysis is needed to understand customers and group customers. One of the data analysis methods used for customer grouping is the K-Means algorithm. This method also helps companies analyze customer loyalty in sales transactions. The purpose of the study is to group customers as an analysis of a business. Data grouping in this study is grouped into 2, namely loyal and less loyal customers. The data in this study is 20 data samples taken from sales transaction data. The results of this study produce information about loyal customers and less loyal customers so that from this information the company can make decisions to improve relationships with customers in making sales transactions